Grafting in Vegetable Crops: A Great Technique for Agriculture - Gaion, Lucas Aparecido [UNESP]; Braz, Leila Trevisan [UNESP]; Carvalho, Rogério Falleiros [UNESP] (Taylor & Francis, 2018)
Grafting is a method employed to improve crop production. The first grafted vegetable seedlings used were for Watermelon (Citrullus lanatus L.) plants grafted onto Lagenaria siceraria L. rootstock to overcome Fusarium wilt. Since then, the use of grafted solanaceous and cucurbitaceous seedlings has spread, with the practice mainly used in Asia, Europe, and North America. The expansion of grafting is likely due to its ability to provide tolerance to biotic stress, such as soilborne pathogens, and to abiotic stresses, such as cold, salinity, drought, and heavy metal toxicity, due to the resistance found in the rootstock. Many aspects related to rootstock/scion interactions are poorly understood, which can cause loss of fruit quality, reduced production, shorter postharvest time, and, most commonly, incompatibility between rootstock and scion. The rootstock and scion cultivars must be chosen with care to avoid loss. This review discusses the possible loss, damage, and potential contribution of grafting and future perspectives of this technique toward improvement of vegetable production.
Keywords: abiotic stress; biotic stress; Cucurbitaceae; rootstock; scion; solanaceae